Key pre-distribution using partially balanced designs in wireless sensor networks. (1st January 2011) - Ruj, Sushmita; Roy, Bimal
We propose two deterministic key predistribution schemes in a wireless sensor network (WSN), in which sensor nodes are deployed randomly. Both the schemes are based on combinatorial designs, called partially balanced incomplete block designs (PBIBD). An important feature of our scheme is that every pair of nodes within communication range can communicate directly, making communication faster and efficient. The number of keys per node is of the order of $\sqrt N$, where $N$ is the number of nodes in the network. Our second design has the added advantage that we can introduce new nodes in the network keeping the key pool fixed. This makes the network scalable. We study the resiliency of the network under node compromise and show that our designs give better results than the existing ones.